Aldose reductase gene polymorphism rs752010122 and retinopathy in type 2 diabetics - Muntaha Maqsood; Palvasha Waheed; Amir Rashid; Asifa Majeed; Ahsan Mukhtar (Journal of the Pakistan Medical Association, 2023)
Objective: To investigate the association of polymorphism in rs752010122 in aldose reductase gene with the pathogenesis of diabetic retinopathy, and to determine the association and allelic frequency between the variant and the disease. Method: The cross-sectional study was conducted from June 2021 to March 2022 at Centre for Research in Experimental and Applied Medicine (CREAM) Laboratory, Department of Biochemistry and Molecular Biology, Army Medical College, in collaboration with the Armed Forces Institute of Ophthalmology, Rawalpindi, Pakistan, and comprised blood samples from subjects of either gender aged 40-70 years. The samples were divided into group I having diabetic retinopathy patients, group II having diabetics without retinopathy, and group III having healthy controls matched for age and gender. The samples were subjected to molecular analysis Results: Of the 150 subjects, there were 50(33.3%) in each of the 3 groups. Variants of aldose reductase rs752010122 polymorphism were significantly associated with a lower risk of diabetic retinopathy (p<0.05). An odds ratio of 1 was noted for both heterozygous and homozygous genotypes (95% confidence interval: 1). Conclusion: Aldose reductase was associated with lower risk of the disease. Key Words: AKR1B1, Diabetes mellitus, Diabetic retinopathy, Single nucleotide polymorphism.